Synoptic analysis of the thermal anomaly for the Days from 1-6, July 2025 in Iraq - Case study - Prof .Dr .Ahmad Mohammed Alhasaan,; Assi. Lect Shimaa Sami Alzinad, (Journal of College of Education, 2026)
The Iraqi atmosphere was exposed, from July 1st to 6th,-2025 to a thermal anomaly, in which temperatures dropped to lower levels than their general averages during this month. This is an anomaly if measured by the high thermal averages for this month. A comprehensive analysis of the fixed pressure levels, specifically the 500 level, showed that. A trough with a polar low over the eastern Mediterranean and northern Iraq helped this situation to remove the control of the upper subtropical high and reduce temperatures, which limits the rise of the hot air mass upwards as a result of reducing the thickness of the atmosphere. This was shown by analyzing the radiosounde charts and data of the Baghdad observation station for the two observations (00 and 1200) Universal Time (03-15). There was a strong local temperature deviation between the 1000 hPa and 500 hPa levels, reaching more than -40°C, which helped cool the surface air mass and lower temperatures. The situation coincided with the sudden activity of the polar vortex during this month, which helped cause polar depressions during July in Iraq
Keywords: Thermal anomaly, European ِAnticyclone, radiosounde, polar trough